Solutions to Lyapunov stability problems of sets: nonlinear systems with differentiable motions - Ljubomir T. Grujic (International Journal of Mathematics and Mathematical Sciences)
Time-invariant nonlinear systems with differentiable motions are considered. The algorithmic necessary and sufficient conditions are established in various forms for one-shot construction of a Lyapunov function, for asymptotic stability of a compact invariant set and for the exact determination of the asymptotic stability domain of the invariant set.